Regulação do livre acesso no transporte de gás natural à luz da ordem econômica da Constituição de 1988 - Silva, Anderson Souza da (2007)
In the middle of modern social changes produced by globalization and capitalism, several markets have changed. States have left the direct coordination of these markets (chiefly public utility sector in the form of monopolies), introducing regulation in order to promote competition. These changes have affected natural gas industry by promoting competition as a key factor to the development and the increase of firms in this market. The regulatory reform of natural gas industry ocurred in EUA and Europe Union and it has produced its first results. In Brazilian context, Constitutional Amendment nbr. 09 and Federal Law nbr. 9.478/97 ( Petroleum Law ) opened the natural gas market to a broad range of private economic agents and they finished the monopoly over the industry before managed by Petrobras. The new regulatory framework of Brazilian natural gas industry has designed competition as a central element to the new form of managment of business and contractual relationships of this industry. Among the regulatory instruments, open access regulation in natural gas pipelines is directed to promote competition. The questions arised about its implementation in Brazilian context are studied in the present work, in which it is discussed the constitutional rules and principles are to be applied to the open access regulation within the theme of statal regulation of economy present in constitutional economic order